2013
DOI: 10.1186/1478-7547-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of a dance intervention for adolescent girls with internalizing problems

Abstract: BackgroundThe increasing prevalence of psychological health problems among adolescent girls is alarming. Knowledge of beneficial effects of physical activity on psychological health is widespread. Dance is a popular form of exercise that could be a protective factor in preventing and treating symptoms of depression. The aim of this study was to assess the cost-effectiveness of a dance intervention in addition to usual school health services for adolescent girls with internalizing problems, compared with usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 26 publications
(39 reference statements)
0
36
0
6
Order By: Relevance
“…Group dance is a social type of physical activity popular with young women. 17 It can be cost effective 18 and is a potentially useful way of positively influencing physical health outcomes 19 and psychological well-being, 20 and increasing self-trust, self-esteem and self-expression in adolescents. 21 There is a need to improve the relatively low self-perceptions of adolescent girls and to reduce the risk of them developing negative ideas about their bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Group dance is a social type of physical activity popular with young women. 17 It can be cost effective 18 and is a potentially useful way of positively influencing physical health outcomes 19 and psychological well-being, 20 and increasing self-trust, self-esteem and self-expression in adolescents. 21 There is a need to improve the relatively low self-perceptions of adolescent girls and to reduce the risk of them developing negative ideas about their bodies.…”
Section: Introductionmentioning
confidence: 99%
“…47,[49][50][51][52][53][54][55][56][57] The economic evidence for such approaches was generally favourable, although there were exceptions. 52,55 Schools-based screening and prevention interventions were examined for anxiety, 58 depression, 47,53,62,63 eating disorders 52,59 and substance use disorders. 60 A UK RCT 61,62 and Australian modelling studies 47,53,63 came to diff erent conclusions about the potential cost-eff ectiveness of schoolsbased prevention strategies for depression, although challenges relating to acceptability and implementation of such strategies were highlighted in both contexts.…”
Section: Resultsmentioning
confidence: 99%
“…In general, there was supportive evidence for family-based interventions, although in several studies, individual therapy or self-help options were suggested to be more cost-eff ective alternatives. 66,68,69 A group delivery context (including in classrooms) was an att ribute of interventions for a range of mental health problems in nine studies, 47,52,58,[60][61][62][63]70,71 again with cost-eff ectiveness evidence that varied between populations. Other att ributes of interventions examined were automated processes, 63 case management, 48,50,65-67 crisis response, 51 fi nancing, 72 holistic care approaches, 48,58,72 information provision, 54,57,61,62,67,69,71 peer support and mentoring 57,71 and staff training and support 49 (Box 4).…”
Section: Resultsmentioning
confidence: 99%
“…In the extensive framework and review conducted by Durlak and DuPre (2008), the perceived need for an innovation as well as perceived benefits of the innovation desired at the local level were found to be consistently related to positive implementation results. Further, the informants expressed that the expected benefits of the innovation came at a relatively low cost, with the perceived promise of rapid results for the target group (Philipsson et al, 2013). This perception explains the interest in the innovation.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study, girls who had participated in the dance intervention expressed that the intervention had given them a feeling of being free, and increased self-trust and confidence (Duberg, Möller, & Sunvisson, 2016). The dance intervention, organized as a complement to the school health services, was demonstrated to be cost-effective compared with usual school health services alone (Philipsson, Duberg, Möller, & Hagberg, 2013). …”
Section: Introductionmentioning
confidence: 99%